The Benefits of Interdisciplinary Instruction in English Language Arts and Social Studies Classrooms - Coehrs, Richard (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
Interdisciplinary instruction using objectives based on English language arts and Social Studies standards has many benefits for students. It strengthens their content area knowledge through inquiry, close reading, the interpretation of multiple sources, authentic writing tasks for an audience or purpose, and critical thinking. Examples of strategies that have produced positive results are presented here in the form of data and analysis from previous case studies. The results of these studies demonstrate how this specific type of interdisciplinary instruction can help students understand that content area knowledge can be transferred and used in innovative ways in fields that may not seem obviously related. This contributes to the advancement of research-based instruction in each of these core content areas of education.